Pengaruh Kualitas Sistem Informasi Akademik, Kualitas Informasi Dan Kualitas Layanan Terhadap Kepuasan Mahasiswa Program Studi Akuntansi - Noer Siti Zahara; Nunung Aini Rahmah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the effect of Academic Information System Quality, Information Quality and Service Quality on Student Satisfaction in the Accounting study program at the Faculty of Economics and Business, Jenderal Achmad Yani University. This study uses quantitative data with a descriptive-associative approach. The analysis technique used is Probability Sampling and Simple Random Sampling with 305 samples from a population of 1,283 active students of the Accounting study program class of 2017-2022. The research data was obtained directly from the original source from the Google form by distributing questionnaires to respondents online. The results showed that partially the Quality of Academic Information Systems had a negative and significant effect on Student Satisfaction, while Information Quality had a positive and significant effect on Student Satisfaction and Service Quality had a positive and significant effect on Student Satisfaction. While simultaneously the Quality of Academic Information Systems, Information Quality and Service Quality have a significant effect on Student Satisfaction. Keywords: Academic Information System Quality, Information Quality, Service Quality